“Can Vaginal Microbiota Act as a Biomarker for the Risk of Gynaecological Precancer and Cancer?” - Bhagyashri Patil Takbhate; Swati Bhakare (Journal of Clinical and Diagnostic Research)
Dear Editor, The female reproductive system hosts unique microbial communities that are crucial for maintaining women’s vaginal health and safeguarding the vaginal environment from numerous genitourinary infections [1,2]. The Vaginal Microbiota (VMB) interacts continuously with both the host and its surroundings, forming a complex system. Recently, the correlation between microbiota and various health conditions has gained considerable attention. While the gastrointestinal microbiota has been the primary focus, research has increasingly explored other areas of the body, including the female genital tract. Dysbiosis in the female genital tract, marked by an imbalance in microbial communities, has been identified as a potential contributor to several gynaecological disorders, like endometriosis, inflammatory diseases of the pelvis, Polycystic Ovary Syndrome (PCOS) and gynaecological malignancies [1]. Disruption of the VMB can trigger inflammation and weaken immune defences, potentially creating conditions conducive to cancer development.